2014
DOI: 10.1111/1467-9566.12104
|View full text |Cite
|
Sign up to set email alerts
|

Touching moments: phenomenological sociology and the haptic dimension in the lived experience of motor neurone disease

Abstract: Currently, there is a relative research lacuna in phenomenological research into the lived experience of motor neurone disease. Based on a sociological research project in the UK, involving 42 participants diagnosed with MND, this article explores the potential of a phenomenological sociology for analysing experiences of this drastically life-limiting neurological disorder. Calls have been made for sociological researchers to analyse more fully and deeply the sensory dimension of the lived body, and this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…Twenty nine articles (Cobb and Hamera, 1986 ; Cox, 1992 ; Young and McNicoll, 1998 ; Brown, 2003 ; Murphy, 2004 ; Hughes et al, 2005 ; Brott et al, 2006 ; Hugel et al, 2006 ; Vitale and Genge, 2006 ; Brown and Addington-Hall, 2007 ; Foley et al, 2007 , 2014a , b ; Fanos et al, 2008 ; King et al, 2009 ; Locock et al, 2009 , 2012 ; Locock and Brown, 2010 ; Gysels and Higginson, 2011 ; O'Brien et al, 2011 , 2012 ; Ozanne et al, 2011 ; Hogden et al, 2012 ; Mckelvey et al, 2012 ; Whitehead et al, 2012 ; Gibbons et al, 2013 ; Mistry and Simpson, 2013 ; Pavey et al, 2013 ; Allen-Collinson and Pavey, 2014 ) were identified following the search. This included a total of 342 patients diagnosed with MND (175 male, 117 female, 50 unknown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty nine articles (Cobb and Hamera, 1986 ; Cox, 1992 ; Young and McNicoll, 1998 ; Brown, 2003 ; Murphy, 2004 ; Hughes et al, 2005 ; Brott et al, 2006 ; Hugel et al, 2006 ; Vitale and Genge, 2006 ; Brown and Addington-Hall, 2007 ; Foley et al, 2007 , 2014a , b ; Fanos et al, 2008 ; King et al, 2009 ; Locock et al, 2009 , 2012 ; Locock and Brown, 2010 ; Gysels and Higginson, 2011 ; O'Brien et al, 2011 , 2012 ; Ozanne et al, 2011 ; Hogden et al, 2012 ; Mckelvey et al, 2012 ; Whitehead et al, 2012 ; Gibbons et al, 2013 ; Mistry and Simpson, 2013 ; Pavey et al, 2013 ; Allen-Collinson and Pavey, 2014 ) were identified following the search. This included a total of 342 patients diagnosed with MND (175 male, 117 female, 50 unknown).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies identified criteria that may have limited patients who had cognitive impairment. For instance, other criteria included patients who were; willing and able to communicate (Gysels and Higginson, 2011 ; King et al, 2009 ), have speech that was understandable (Ozanne et al, 2011 ), have English language conversational skills (Brott et al, 2006 ), or be able to “participate” (Allen-Collinson and Pavey, 2014 ). No additional reference within studies was given to the possible influence of cognitive impairment on results.…”
Section: Resultsmentioning
confidence: 99%
“…To meet the aim of the current research, hermeneutic (interpretive) phenomenology was used as a methodology, as this is suitable for studying lifeworld experiences (Finlay, ). Finlay (, p. 89) suggests “both descriptive and hermeneutic (interpretive) designs may be used to explore how everyday experience shows itself in the lifeworld, i.e., as embodied and lived through time/space and in relationships with others.” Descriptive phenomenology as a methodology offers researchers an approach through which to explore body experiences and a researcher “brackets” their existing presuppositions (experiences and beliefs) of a phenomenon to promote validity (Husserl, 1989 cited in Allen‐Collinson & Pavey, ). Hermeneutic (interpretive) phenomenology as a methodology offers an approach through which to explore the body experience and how this impacts upon everyday lives, and a researcher brings their prior presuppositions of a phenomenon to the “hermeneutic circle” of understanding (Finlay, ; Heidegger, 1927/1962).…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the onset of MND, the ecstatic body provides the main means of an individual reaching out to engage with and experience the world, including via the senses (Allen-Collinson and Pavey 2014, Legrand 2007, Leder 1990. When the body begins to 'dysfunction', the previously 'silent', recessive body, then appears to consciousness, or 'dys-appears' (Leder 1990).…”
Section: Different Modes Of Bodily Beingmentioning
confidence: 99%
“…The recessive body refers to the hidden, inner body of internal organs and processes of which we are not usually aware, such as respiration and digestion. In contrast, the ecstatic body is defined as the 'out-standing' body that projects outward into its environment and is aware of itself via feedback mechanisms.Prior to the onset of MND, the ecstatic body provides the main means of an individual reaching out to engage with and experience the world, including via the senses (Allen-Collinson and Pavey 2014, Legrand 2007, Leder 1990. When the body begins to 'dysfunction', the previously 'silent', recessive body, then appears to consciousness, or 'dys-appears' (Leder 1990).…”
mentioning
confidence: 99%